Kebijakan Pemerintah Daerah Bali dalam Mewujudkan Penyelenggaraan Pelayanan Kesehatan Tradisional Integrasi - I Made Adi Widnyana; Ni Ketut Kantriani; Yoga Siwananda (Fakultas Hukum, Universitas Warmadewa, 2024)
Progress and changing ages have an impact on changes in various areas of life, one of which is health. A variety of cutting-edge discoveries related to medical methods and medicines led to advances in both conventional and traditional health care. This development has led to various policies made by countries including Indonesia. Indonesia sheds health-related policy as a constitutional right of the people as set forth in the rules of enforcement. The guarantee of good health care gives the public the right to use the kind of medical or traditional health care. There are three types of traditional health care within the rules of enforcement: empirical, complementary, and integrated. This paper highlights the integration of traditional health services which, based on the authority of the Indonesian Government Regulations, mandate local governments to make regional policies that are in line with national policies. This writing uses normative methods with a legislative and conceptual approach. The results showed that the policy of the regional government of Bali in the maintenance of traditional health services integration implemented by issuing the regulation of the governor of Bali No. 55 Year 2019 on the traditional health service of Bali which provides guarantees on the implementation of health services traditional integration of bali as a collaboration carried out between the traditional complementary health services with conventional health services in health services facilities such as Puskesmas and hospitals. Progress and changes of the era have an impact on related types of traditional health services the integration given in its organization is established on the basis of the Decision of the Governor of Bali of the results of the analysis of the study team which is further established by the respective heads of the health service facilities.